Establishing reactivity descriptors for platinum group metal (PGM)-free Fe-N-C catalysts for PEM fuel cells - Kucernak,A; Mehmood,A; Malko,D (Energy and Environmental Science, 2020)
We report a comprehensive analysis of the catalytic oxygen reduction reaction (ORR) reactivity of four of today's most active benchmark platinum group metal-free (PGM-free) iron/nitrogen doped carbon electrocatalysts (Fe–N–Cs). Our analysis reaches far beyond previous such attempts in linking kinetic performance metrics, such as electrocatalytic mass-based and surface area-based catalytic activity with previously elusive kinetic metrics such as the active metal site density (SD) and the catalytic turnover frequency (TOF). Kinetic ORR activities, SD and TOF values were evaluated using in situ electrochemical NO2− reduction as well as an ex situ gaseous CO cryo chemisorption. Experimental ex situ and in situ Fe surface site densities displayed remarkable quantitative congruence. Plots of SD versus TOF (“reactivity maps”) are utilized as new analytical tools to deconvolute ORR reactivities and thus enabling rational catalyst developments. A microporous catalyst showed large SD values paired with low TOF, while mesoporous catalysts displayed the opposite. Trends in Fe surface site density were linked to molecular nitrogen and Fe moieties (D1 and D2 from 57Fe Mössbauer spectroscopy), from which pore locations of catalytically active D1 and D2 sites were established. This cross-laboratory analysis, its employed experimental practices and analytical methodologies are expected to serve as a widely accepted reference for future, knowledge-based research into improved PGM-free fuel cell cathode catalysts.